Implementasi Model Interaktif dalam Meningkatkan Pemahaman Spiritualitas Pemuda Jemaat GKSI Trimorejo - Patricia Wira Lestari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The spirituality of today’s church youth encounters multidimensional challenges, particularly the pervasive influence of digital culture, the gradual decline in interest toward spiritual disciplines, and the weakening of involvement in ecclesial ministry. Such dynamics often create a gap between theological knowledge and lived faith experiences. This Community Service (PkM) initiative was designed to respond to these issues by implementing an interactive model aimed at enhancing the spiritual understanding of the youth at GKSI Trimorejo Congregation. The model emphasizes participatory learning processes, in which youth are not merely passive recipients of teaching but active contributors to collective faith formation. The methodological framework consisted of three main stages: initial observation to identify needs and spiritual conditions; preparation of training modules contextualized with the congregation’s realities; and the implementation of interactive activities such as group discussions, thematic Bible studies, role-play, and collective reflection. Evaluation strategies integrated both quantitative and qualitative approaches, including pre-tests and post-tests to measure cognitive growth, alongside participatory interviews to capture experiential insights. The findings reveal a notable increase in youth comprehension of biblical principles, heightened enthusiasm and participation in church programs, and the establishment of a more cohesive spiritual learning community. Furthermore, the process encouraged a deeper sense of belonging and responsibility among the participants toward their ecclesial environment. In conclusion, the interactive model demonstrates significant effectiveness in fostering youth spirituality and may serve as a viable alternative strategy for churches encountering similar challenges within contemporary contexts of ministry.